Leave Management System (LMS) / Chan Yim Khim - Chan , Yim Khim (2001)
This project attempts to further enhance and develop new features and functionalities for the existing Leave Management System (LMS) in the Faculty of Computer Science and Information Technology (FCSIT). The existing LMS is a web-based application designed to automate leave processing system in the faculty. Briefly, this project strives to test the efficiency of the system, to ease the process of leave application, to make the system user-friendlier, and to enhance the integrated system with the Attendance Management System (AMS). Its significance includes higher quality of the system in terms of its efficiency and effectiveness, faster processing time, and having a centralized management of corporate resource holdings. In addition, LMS is hoped to project the main idea of a Generic Office Environment of promoting a thorough paperless environment with the routing of information through workflow applications. The proposed methodology encompasses enhancements of the current system, as well as development of new functionalities. This came about from review of literature, whereby it has cited considerable feedback and recommendations from various sources. From there, a thorough analysis is done to find out the feasibility of this project. After determining that the project is feasible, the approach suggested would be the spiral model, where flexibility is the main advantage in coming up with enhancements and new developments. Systems designs with appropriate diagrams and tables are given to describe the system. With the systems designs at hand, the system is implemented and developed accordingly. Step-by-step guidelines are provided to ensure clarity and avoid ambiguity. In order to test the accuracy and reliability of the system, testing is done in five phases; Wlit testing, module testing, interface testing, integration testing, and lastly system testing. Lastly, the system is evaluated in terms if its strength and limitations. Problems uncovered during the evaluation period are discussed, and solutions to overcome those problems are provided. After overcoming a myriad of challenges, this project has smoothen the processing of leaves without any more hiccups, enable up-to-date information retrieval, complete an optimized database, and include more input controls in the system. As such, it is hoped that it will serve the faculty better and fulfill its aim in having a Generic Office Environment.